Effect of 60NM Polystyrene Latex Nanopartcles Concentration Towards Calculation of Measurement Uncertainty and Z-Score in Particle Size Analysis Using Dynamic Light Scattering Principle - Dyana Zakaria, Nor; Zahidah Abdul Karim, Izzati; Ahmad, Azimah; Osman, Sabariah; Balakrishnan, Venugopal (International Journal of Engineering and Technology, 2018)
The dynamic light scattering technique is used to determine the particle size distribution macro and nanomolecules in colloids. The determination of size is crucial for some of the application such as nanogold production for in-vitro diagnostic raipd test kit production. The measurement of the size is very crucial as diffent size of particle will prodive different applications propose. Therefore, during the measurement the important point of consideration is the measurement of uncertanity which contributes to the ultimate measurement of the size. There few aspect that is being considered in the measurement of uncertanity, which are reference standard, resolution, dift value of equipment and concentration of sample. However, in this study we measure the size distribution of polystyrene latex sphere (PLS) of 60nm at different concentration of 1 drop to 20 drop in 1ml of 10mM of NaCl. The experiment was carried out to prove that the concentration does not affect the measurement particle size when measured using hydrodynamic size distribution calculation. The result indicates the measurement of particle size of 1 drop to 20 dorp of PLS was in the range of 64.53 to 65.62, which is in the range of hydrodyanamic size of the standard PLS. Therefore, the concentration does not affect the measurement of the particle size and the effect of concentration can be ommited from the measurement of uncertanity calculation.Â Â Â